Implementation of the value of legal use in preventing drug abuse through the Legal Awareness Family (Kadarkum) Contest - Laskarwati, Batari (Universitas Negeri Semarang, 2018)
The Legal Awareness Family (Keluarga Sadar Hukum, Kadarkum) is one of the programs to increase public awareness of the dangers of drug abuse. One form of this program besides socialization and education, also intensive assistance to every family, so that the Indonesian -free Indonesian program can be achieved through a program that starts from the smallest environment. In Central Java, victims of drug abuse and drugs in Central Java in 2017 reached more than 523 thousand people. This paper discusses how Kadarkum can run optimally as a prevention in drug abuse.